A room full of chocolate A story of friendhsip,family,and post-bellied pigs. - Elson, Jane (london Hodders childrens book, 2014)
Grace's fun-loving Mum has found a lump. Her north London world of sleepovers, tap dancing and playing the clarinet fall apart when she is sent to live with her grumpy old granddad on his farm in Yorkshire while her mother goes into hospital to get better. Grace misses her mother so much it hurts, and doesn't quite understand what is happening to her. And things go from bad to worse when she starts school and becomes the bullies' latest target. But Grace is no longer alone when she meets Rainbow Girl Megan and her pig, Claude - when she's with them she feels as if she can confront anything. At Easter time when Grace misses her mum the most, she knows she must find a way to get to London. With Megan's help, she hatches a plan to run away that involves Claude, chocolate Easter eggs and a risky ID swap. But it's all worth it if it means that she finally gets to see her mum